Language and Ageing--Exploring Propositional Density in Written Language--Stability over Time - Spencer, Elizabeth; Craig, Hugh; Ferguson, Alison; Colyvas, Kim (Clinical linguistics & phonetics, 2012)
This study investigated the stability of propositional density (PD) in written texts, as this aspect of language shows promise as an indicator and as a predictor of language decline with ageing. This descriptive longitudinal study analysed written texts obtained from the Australian Longitudinal Study of Women's Health in which participants were invited to respond to an open-ended question about their health. The 635 texts used for this study were taken from 127 middle-aged women who responded to this question on each of the five surveys conducted at 3-year intervals over a 16-year period. The study made use of an automated PD rater (CPIDR-3) for the analysis. PD was found to be a stable measure over time when comparing the grouped data, but there was between- and within-subject variation over time. Further research is needed to explore the valid use of this measure in research into language and ageing. (Contains 2 figures and 4 tables.)